Research on Robust Control for Electrified Railway Harmonic Suppression - Xu, Xiangzheng (Elektronika ir Elektrotechnika, 2013)
Because of using the nonlinear high-power load, the electrified railway has serious harmonic problems. Aiming at the electrified railway power quality problems, this paper has established averaging active power filter model, and designed the H-infinity controller. Through containing all kinds of disturbance, ensure active power filter to approaching track complex current signal, thus improve the robustness of systems. Simulation results show that electrified railway harmonic control effect is good based on H-infinity control. Under parameter perturbation, THD relatively small changes, the system has strong robustness. In comparison with the hysteresis controller, H-infinity controller has a better control effect. Therefore, based on H-infinity control of active power filter in electrified railway harmonic control has wide application prospects. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3694